An Italian education - Parks, Tim (Secker & Warburg, 1995)
Tim parks focuses on his own young children in the small village where he lives, to build a fascinating picture of the contemporary Italian family : its bizzarre foibles and extraordinary solidity, its peculiar ceremonies- at school, at home, at work and play- and its profound moral schizophrenia